PWE-077 Biofeedback: time to let the dietitian join the service?. (June 2019) - Brundrett, Diane; Vernon, Nicola; Patterson, Rachel
Abstract : Introduction: In 2015 a new dietetic service was established to provide dietary modification including low FODMAP advice for patients as part of the biofeedback service for patients with functional bowel disorders such as faecal incontinence and evacuatory disorders. Studies have reported the effectiveness of diet in IBS 1, 2 but no research has investigated diet in the biofeedback. The aim of this audit was to evaluate the effect on patient outcomes of dietary intervention in this new biofeedback service (BF) and compare it to the established dietetic gastroenterology clinic (GC). Methods: A retrospective audit was undertaken on the effect of personalised dietary advice. At the first appointment patients were asked to complete the gastrointestinal symptom rating scale (GSRS) and answer the question 'do you currently have satisfactory relief of your gut symptoms. These were repeated at each review. Patients were screened and given first line advice or low FODMAP advice or first line advice followed by low FODMAP if first line did not result in satisfactory relief of symptoms. Comparisons were made on effectiveness of dietary intervention in and between the two clinics. Results: A total of 46 patients were included (22GC:24BF). Mean age 54±16years, 8M:38F. Dietary advice provided: first line (22%), low FODMAP (63%), first line and then low FODMAP (15%). Dietetic intervention led to improvements in symptoms in both clinics. More patients in the BF (54%) reported satisfactory relief of their symptoms compared to the dietetic GC (41%). Improvement was evident for all symptoms (Table 1 ) and is comparable between the two clinics, although improvement in abdominal bloating was notably higher in BF Conclusion: Our audit highlights the role of a dietitian within a biofeedback multi-disciplinary service and that dietary advice including first line advice and the low FODMAP diet can improve symptoms in patients with faecal incontinence and evacuatory disorders as well as IBS. References: McKenzie, et al. ( 2012) BDA evidence-based guidelines for the dietary management of irritable bowel syndrome in adults. J Hum Nutr Diet 24, 260 NICE (2008) Irritable bowel syndrome in adults. Diagnosis and management of irritable bowel syndrome in primary care. https://www.nice.org.uk/guidance/cg61/resources/irritable-bowel-syndrome-in-adults-diagnosis-and-management-pdf-975562917829